Tensile test machine for unsymmetrical materials - Sharifishourabi, G. (Springer, 2014)
A novel solution to overcome the shortcoming of conventional tensile test machines in dealing with unsymmetrical materials and off-axis testing of composites is presented. Conventional testing machines are designed on the basis of subjecting a specimen to axial load to determine the stiffness and strength of the material. For specimens with unsymmetrical cross-section this method is no longer valid due to induced additional bending stresses. To overcome this problem a novel tensile test machine was designed, which allows bending deformation, thus subjecting the specimen to pure tension instead of axial loading. To validate the design, the machine was fabricated and employed for tensile testing of an aluminum specimen with unsymmetrical cross-section. The comparison of test results from a conventional machine and from analytically calculations, based on pure tension, reveals that conventional machine generates significant errors, while the results from new machine are in good agreement. The machine was then used to test a functionally graded beam.